Distribution of wood feeding termites in the primary and regenerating forests of Danum Valley, Lahad Datu, Sabah - Kevin Fernandez A/L Shellton Fernandez (2015)
The tendency of wood feeding termites selecting types of tree species as their food source is still unclear. This study was aimed to understand the distribution patterns of termites especially wood feeding termites and the types of tree species which are infested from the primary and regenerated forest of Danum Valley. The objectives of this study were to i) determine the species of wood feeding termites associated with trees in the forest of Danum Valley; ii) identify the types of trees in the primary and regenerated forest associated with termites; iii) map the distribution patterns of termites in the forest of Danum Valley; iv) find the relationship between termites and abiotic factors from the forest of Danum Valley. This research was carried out in two types of forest namely primary and regenerated forest in Danum Valley, Lahad Datu, Sabah. A total of six plots were sampled in this study. Three plots with an area of 0.25 hectare (SO meters X 50 meters) were placed in each, primary and regenerated forest. Trees in each plot with a diameter breast height, (dbh) of more than 10 cm were examined. Examination for termites on trees included examination of tree barks, runways and termite mounds. Trees with and without termites were tagged and labeled accordingly using GPS. Overall a total of 23 termite species were sampled from the forest of Danum Valley. However, only 16 species (69.6%) of termites sampled were wood feeding termites. Shannon-Wiener Diversity Index and Simpson's Index of Diversity indicates that termites in the regenerated forest {H' = 2.5909; D = 0.9374) were higher compared to the primary forest (H' = 2.5335; D = 0.9312). There were a total of 66 interactions of which involved 23 termite species and 31 tree species. Termites in Danum Valley were found in association with tree families of Alangiaceae, Annonaceae, Burseraceae, Dipterocarpaceae, Ebenaceae, Euphorbiaceae, Fabaceae, Fagaceae, Lauraceae, Magnoliaceae, Meliaceae, Myrsinaceae, Sapindaceae and Sapotaceae. Macaranga gigantea was the highest recorded tree species with 16 hits found associating with nine different termite species. This tree species was only sampled in the regenerating forest with 54 hits. Macrotermes ma/accensis is the termite species which are abundantly found in the forest of Danum Valley. This species was found associated with six different tree species. Eight termite pest species which have been identified as potential pest in Danum Valley include Heterotermes tenuior, Coptotermes cutvignatus, Schedorhinotermes medioobscurus, Schedorhinotermes sarawakensis, Microcerotermes dubius, Macrotermes gilvus, Odontotermes Javanicus and Nasutitermes matangensis. Statistical analysis showed that termites association with trees in the forest of Danum Valley are influenced by dbh (p = 0.000) and canopy density (p = 0.006). However, the presence of pest termites is statistically influenced by dbh (p = 0.001) and soil pH (p = 0.002).